Too close for comfort. Issue 3 (3rd June 2013) - Broadribb, Michael P.
<x xml:space="preserve">Abstract</x> Learning from experience is one of the four pillars of Risk‐Based Process Safety [CCPS, Guidelines for Risk Based Process Safety, New York, 2007]. Incidents that occur at one facility often provide opportunities to strengthen management systems at other facilities. Sharing the technical lessons learned from incidents is morally right and vital to improving process safety performance across the process and related industries. Most incidents also involve human factors, often as a key causal factor. Understanding these performance shaping factors can also be essential to minimizing future failures. Most articles regarding case studies on process safety incidents are written and presented by a third party who was not directly involved in the incident. As such, the articles may lack the human element and other insights that can only be properly appreciated and articulated by someone directly involved in the incident. In his early career the author was involved in two major incidents while managing the day‐to‐day operation of refinery process units. This article describes the first incident involving two major fires. In both incidents, the author found himself decidedly too close for comfort and could easily have become a casualty himself. This article will raise awareness of lessons learned relating to a number of elements of Risk‐Based Process Safety [CCPS, Guidelines for Risk Based Process Safety, New York, 2007] and human factors. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 255–259, 2013